MSME’S Demographic As Moderation In The Impact Of Perception And Understanding Of Bookkeeping Towards Quality Of Financial Report - Sari, Cahyani Tunggal; Pahlawi, Lukman Ahmad Imron (Economics and Business Solutions Journal, 2019)
Micro Small Medium Enterprises (MSME) especially in culinary are the main destination of tourist in Surakarta Indonesia. As the tourist destination, MSME must be creative in develop their product. The financial ability is the main source of the owner in develop their business. Bank loan is an alternative in order to improve the financial sorce. Therefore, the MSME s owner need to compile the financial report as one of bank loan requirement. This study is a quantitative research which is use multiple regression analysis using moderation variables. The quality of financial report is the dependent variable. The Independent variables are the MSME s owner perception and understanding about book keeping. This study also enclose the MSME s owner demographic background that consist of educational leverage and business size as the moderating variables. The data is collected from culinary MSME s in Surakarta, Indonesia in the year of 2017. The findings of this research shows that educational leverage and business size are Predictor Moderation Variable. Besides, the perception and understanding are not significantly influence the financial report quality. The result of beta value shows that the business size strengthen the bookkeeping perception variable and weaken the understanding variable towards financial report quality. While the educational leverage strengthen the understanding variable and weaken the perception variables even all of them are not significantly influenced.